The spoils of war greed, power, and the conflicts that made our greatest presidents - Bueno de Mesquita, Bruce (New York PublicAffairs, 2016)
It's striking how many of the presidents Americans venerate--Abraham Lincoln, George Washington, Franklin D. Roosevelt, and John F. Kennedy, to name a few--oversaw some of the republic's bloodiest years. Perhaps it's because they looked out for important political causes. Or maybe they just looked out for themselves. This revealing and entertaining book puts some of America's greatest leaders under the microscope, showing how their calls for war, usually remembered as brave and noble, were in fact selfish and convenient. In every case, our presidents chose personal gain over national interest while loudly evoking justice and freedom. The result is an eye-opening retelling of American history, and a call for reforms that may make the future better. In this book, Bruce Bueno de Mesquita and Alastair Smith show that even leaders who proclaim the loftiest of intentions have concerns and motives that are far less pure than we might like. You'll never look at politics the same way again
Includes bibliographical references and index.
Keywords: Presidents--United States--History.